THE STUDY OF LANGUAGE AND CULTURE IN A GLOBALIZED WORLD (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article discusses the study of language and culture in a globalized world. This article examines the significance of the English language in the current process of globalization, where languages and cultures increasingly influence each other. It explores how modern technologies, the internet, and the growing interactions between nations contribute to this phenomenon. Representatives of different nations become familiar with each other’s values, lifestyles, and cultures. Today, English is becoming an international means of communication and plays a crucial role in enhancing friendly dialogue and relations between countries.